The Differences in Executive Function, Protein Intake, and Daily Activities Function of Elderly Living in Urban and Rural Area - Christa Vidia Rana Abimanyu (Universitas Katolik Soegijapranata, 2020)
Person in the elderly life phase will naturally experience a decrease in bodily functions either due to natural degenarive process or disease. The brain is one part of body that has decreased function. Previous study has shown that a strong decline in executive function can reduce the ability of the elderly to plan, organize, self control, and become aware of problems, which will affect the decrease in the capacity of the elderly to carry out daily activities. The good news is, other studies have shown that the decline in brain performance can actually be inhibited by proper protein intake. Instruments used for daily activities using ADLI and IADL; executive function was measured with the TMT A and B battery test, Digit Span, and Five Point Test which have been adapted to Indonesian; nutritional status using Waist:Hip Ratio; and Protein supply using 24-h Recall. The Mann-Whitney test Technique reveals that (1) there is no difference in executive function in urban and rural elderly; (2) there is no difference in protein intake among urban and rural elderly. However, it was found that (3) there was a significant difference between ADL in Urban and rural Elderly with Z = -2.083 (p=0.0037, < 0,05) and the ADL function of the elderly in the village was higher (M=12,5) than the function. ADL among the elderly in urban areas (M=7,5)